Conceptualizing Mentorship in Contemporary Professional Settings - Nathan R. Vann; Mitsunori Misawa (Adult Education Research Conference, 2022)
Although there are many mentorship-related scholarships, there is still a lack of understanding of how mentorship is implemented effectively in professional settings. This paper explores mentorship strategies in workplaces.
Keywords: mentorship; workforce development; professional adults